2019
DOI: 10.1016/j.isci.2019.09.020
|View full text |Cite|
|
Sign up to set email alerts
|

RARβ Agonist Drug (C286) Demonstrates Efficacy in a Pre-clinical Neuropathic Pain Model Restoring Multiple Pathways via DNA Repair Mechanisms

Abstract: SummaryNeuropathic pain (NP) is associated with profound gene expression alterations within the nociceptive system. DNA mechanisms, such as epigenetic remodeling and repair pathways have been implicated in NP. Here we have used a rat model of peripheral nerve injury to study the effect of a recently developed RARβ agonist, C286, currently under clinical research, in NP. A 4-week treatment initiated 2 days after the injury normalized pain sensation. Genome-wide and pathway enrichment analysis showed that multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…This functional recovery required NG2 + cells near the neuronal cells to produce RA by activating ALDH1a2 in response to the RARβ agonist (121). Synthetic RARβ agonists also showed efficacy in preclinical neuropathic pain models (27,122). From the publications summarized here, it is clear that synthetic RARβ agonists should continue to be tested for efficacy in models of various types of neuronal injuries and in models of neurodegenerative disorders (123).…”
Section: Learning and Memory Neuronal Injury And Synthetic Retinoid A...mentioning
confidence: 89%
“…This functional recovery required NG2 + cells near the neuronal cells to produce RA by activating ALDH1a2 in response to the RARβ agonist (121). Synthetic RARβ agonists also showed efficacy in preclinical neuropathic pain models (27,122). From the publications summarized here, it is clear that synthetic RARβ agonists should continue to be tested for efficacy in models of various types of neuronal injuries and in models of neurodegenerative disorders (123).…”
Section: Learning and Memory Neuronal Injury And Synthetic Retinoid A...mentioning
confidence: 89%
“…Overall stress provoked by neuropathic pain and its concurrent inflammatory response has been linked to a large number of persisting adaptations at both cellular and molecular levels [27]. Among these, we highlight the occurrence of profound gene expression changes, though the underlying mechanisms by which these alterations are induced remain poorly understood [27,28]. Some studies, however, suggest that the inflammatory response is one of the main factors responsible for such DNA damage [21,29], while other authors have demonstrated that even neuronal activity can be enough to induce highly toxic DNA lesion, which may alter the expression of late response genes [30].…”
Section: Discussionmentioning
confidence: 99%
“…The RARβ agonist drug C286 24 also demonstrates efficacy in a pre-clinical neuropathic pain (NP) model restoring multiple pathways via DNA repair mechanisms. 47 …”
Section: Rarβ Agonistsmentioning
confidence: 99%
“…Using a rat model of peripheral nerve injury it has been found that a 4-week treatment with C286 24 initiated 2 days after the injury normalised pain sensation. 47 Genome-wide and pathway enrichment analysis showed that multiple mechanisms persistently altered in the spinal cord were restored to preinjury levels by the agonist. 47 …”
Section: Rarβ Agonistsmentioning
confidence: 99%
See 1 more Smart Citation